Moving People to Help People Move - Graftieaux, Pierre (Elsevier, 2018)
The 24-km Dakar Toll Road (Autoroute de l’Avenir Dakar – Dianmiadio), built to solve severe congestion problems, was inaugurated in 2013 on schedule and below budget. It has reduced travel times by two thirds between downtown and the outskirts and is spurring the development of the conurbation. Long recognized to be an urgent priority, it took however about 30 years to eventuate, mainly because decision makers were deterred by the magnitude of the resettlement plan needed to insert this infrastructure into densely populated informal settlements. The paper explains (i) how the relocation of 38,000 people was mitigated through a comprehensive compensation scheme combined with the construction of a new town to accommodate some of those relocated, and the upgrading of low-income settlements along the Road and (ii) how this USD760 million project, first greenfield toll road in Sub-Saharan Africa (excluding South Africa), and structured as a Public Private Partnersip, materialized through funding from multilaterals, government, commercial banks and the private sector. The paper describes how compensation of affected households, commercial buildings, etc. were estimated, making sure all those affected end up in at least an equivalent position as they were in prior to the project. It also explains how a new city was designed to accommodate 20,000 persons, with schools, health centers, paved roads, community facilities, running water, electricity, market, sewage, etc. In addition, it details the rationale for providing consolidated settlements along this road with better urban roads, community facilities and drainage structures, to ensure that those who are too poor to drive, would still benefit from the project.